Insidensi Bayi Berat Lahir Rendah pada Spektrum Plasenta Akreta di Rumah Sakit Dr Hasan Sadikin Bandung - Kharisma, Yuktiana; Agustina, Hasrayati; Suryanti, Sri; Dewayani, Birgitta Maria; Hernowo, Bethy Suryawati (Jurnal Kesehatan Andalas, 2022)
Low birth weight (LBW) babies are closely related to infant morbidity, stunted growth and cognitive development, and chronic diseases. Placenta accreta spectrum (PAS) is a condition that complicates pregnancy and is closely related to low birth weight. Objectives: To determined the incidence of LBW in mothers with SPA at the hospital Dr. Hasan Sadikin Bandung. Methods: A descriptive observational study involving 71 cases of SPA in hospitalsÂ  Dr. Hasan Sadikin Bandung, period 2016-2020, which has met the inclusion and exclusion criteria. SPA cases were divided into three groups: placenta accreta, increta, and percreta. In each SPA group, the incidence of LBW was evaluated. Results: 46.5% (33/71 cases of PAS) had low birth weight, while 53.5% (38/71 cases of PAS) had normal birth weight babies. The placenta accreta and percreta groups were dominated by normal birth weight infants [(18/31 cases), (5/9 cases)], while the placenta increta group was dominated by low birth weight infants (16/31 cases). The LBW category is divided into Extremely Low Birth Weight (ELBW), Very Low Birth Weight (VLBW), and LBW. In placenta accreta, there were 2 ELBW and VLBW infants, and 9 LBW infants. In the placenta increta, there are 3 ELBW and VLBW, and 10 LBW. In the placenta percreta, there were 1 ELBW and 3 LBW, while VLBW was not found in the placenta percreta. Conclusion: The incidence of LBW is found in almost half the population of SPA cases in hospitals. DR. Hasan Sadikin in the 2016-2020 period.Keywords: Â low birth weight, placenta accreta spectrum